Comparative Study between FACTS Devices for Power System Transient Stability Improvement with Solar Photovoltaic. - Ikram BOUCETTA; Djemai NAIMI (My University, 2020)
In this paper, a study on the transient stability of power system was performed by using several types of FACTS (Flexible AC Transmission System) such SVC, STATCOM and UPFC, particularly when integrating a significant amount of electrical energy produced by renewable sources, exactly by solar photovoltaic sources. This study is applied on the famous 30 bus IEEE test system, under the Power System Analysis Toolbox (PSAT) simulation software. Based on the critical clearing time (CCT) as a stability index, the simulation results clearly showed the improvement of network stability with superiority in favor of the UPFC over STATCOM and SVC.
Intervention
Keywords: transient stability; FACTS; solar photovoltaic; PSAT; CCT